Influence of Binasal and Uninasal Inhalations of Essential Oil of Abies koreana Twigs on Electroencephalographic Activity of Human. (30th November 2016) - Seo, Min; Sowndhararajan, Kandhasamy; Kim, Songmun
Abstract : Objectives . The present work investigates the effect of essential oil from the twigs of Abies koreana on electroencephalographic (EEG) activity of human brain in order to understand the influence of binasal and uninasal inhalations. Methods . To accomplish this study, the essential oil from the twigs of A. koreana (AEO) was isolated by steam distillation and the EEG readings were recorded using QEEG-8 system from 8 grounding electrodes according to the International 10-20 System. Results . D-Limonene (25.29%), bornyl acetate (19.31%), camphene (12.48%), α -pinene (11.88%), β -pinene (6.45%), and eudesm-7(11)-en-ol (5.38%) were the major components in the essential oil. In the EEG study, the absolute alpha (left frontal and right parietal) and absolute fast alpha (right parietal) values significantly increased during the binasal inhalation of AEO. In the uninasal inhalation, absolute beta and theta values decreased significantly, especially in the right frontal and left and right parietal regions. The results revealed that the AEO produced different EEG power spectrum changes according to the nostril difference. Conclusion . The changes in EEG values due to the inhalation of AEO may contribute to the enhancement of relaxation (binasal inhalation) and alertness/attention (right uninasal inhalation) states of brain which could be used in aromatherapy treatments.